2016
DOI: 10.1182/blood-2015-02-629667
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl oxidase is associated with increased thrombosis and platelet reactivity

Abstract: • Mice overexpressing LOX in platelets have more severe thrombosis than normal animals.• LOX expression influences platelet adhesion to collagen. ) were generated. Pf4-Lox tg/tg mice had a normal number of platelets; however, time to vessel occlusion after endothelial injury was significantly shorter in Pf4-Lox tg/tg mice, indicating a higher propensity for thrombus formation in vivo.Exploring underlying mechanisms, we found that Pf4-Lox tg/tg platelets adhere better to collagen and have greater aggregation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 59 publications
1
30
0
1
Order By: Relevance
“…1B and fig. S1E) (20) and was validated by the presence of an occlusive thrombus at the site of injury (Fig. 1C).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…1B and fig. S1E) (20) and was validated by the presence of an occlusive thrombus at the site of injury (Fig. 1C).…”
Section: Resultsmentioning
confidence: 79%
“…The antithrombotic effects of the above agents were weighed against the bleeding risk using the standard tail vein transection model (20). Because STUB1 modulation normalized the thrombotic risk to non-CKD range, we compared YL-109–mediated alteration in bleeding time to probenecid (non-CKD) controls.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that LOX is associated with tumor malignancy, especially with distant metastasis that includes bone metastasis, in several types of cancers such as thyroid, breast, nasopharyngeal, gastric and pancreatic cancers. 23,24,27,[34][35][36][37] With reference to HCC, some reports have shown an association between LOX and angiogenesis markers such as vascular endothelial growth factor (VEGF), but none has revealed an association with EMT or metastasis in HCC. We exhaustively examined the role of LOX in HCC using a large transcriptome matrix, which showed that high LOX expression is closely associated with EMT.…”
Section: Discussionmentioning
confidence: 99%
“…33 In patients with chronic myeloproliferative neoplasia and thrombosis there is an increased level of lysine oxidaze-LOX, the enzyme that contributes to platelet activation and influences platelet receptor function for collagen. 34,35 Numerous studies have shown a high oxidative status in patients with chronic myeloproliferative neoplasms, a situation that correlates with a higher thrombotic risk. 32,36,37 Although associations of increases in oxidative stress with MPN have been identified, association with changes in membrane fluidity and thrombocyte function remains to be investigated.…”
Section: 32mentioning
confidence: 99%